The cloud factory I: generating resolved filamentary molecular clouds from galactic-scale forces - Smith, Rowan J.; Treß, Robin G.; Sormani, Mattia C.; Glover, Simon; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. We introduce a new suite of simulations, ‘The Cloud Factory’, which self-consistently forms molecular cloud complexes at high enough resolution to re
Gesehen am 17.02.2020
Advance access publication 2019 December 2